Optimization of Judicial Supervision in Indonesia: Challenges and Solutions in Maintaining Judicial Independence and Integrity - Kadir, Adies; Gunarto, Gunarto; Suwarno, Suwarno (UNISSULA, 2025)
Supervision of judges in Indonesia is a crucial element to maintain the integrity, independence, and professionalism of the judicial system. This study anayzes the effectiveness of the judicial oversight mechanism through an internal approach by the Supreme Court, external by the Judicial Commission, and the role of the community through a code of ethics. With a qualitative descriptive-analytical approach, this study uses secondary data from legal documents, such as the 1945 Constitution, Law Number 48 of 2009, and the Joint Regulation of the MA-KY 2012, as well as interviews with judges and academics. The results of the study indicate that the MA's internal supervision is constrained by a large workload, while the KY's supervision is limited due to the Constitutional Court Decision Number 005/PUU-IV/2006, which excludes MK judges and supreme court justices, triggering the risk of judicial corruption and a crisis of public trust. Public supervision through a code of ethics is effective but requires further education. The main challenges include overlapping authority between the MA and KY and the lack of supervisory integrity. This study recommends better coordination, strengthening the authority of the KY, and increasing the role of the community to ensure justice and judicial independence.